UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN JARAK PAGAR (Jatropha curcas Linn) PADA BERBAGAI KONSENTRASI TERHADAP PERTUMBUHAN BAKTERI Pseudomonas aeruginosa - nyoman mastra (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2021)
Background, Pseudomonas aeruginosa is the main bacterium in nosocomial infections. Pseudomonas aeruginosa is a bacterium that is resistant to almost all of antibiotics. As a result of these resistance cases, it is necessary to find the alternative products derived from natural ingredients antibacterial agents, one of which is Jatropha leaves. Objective, the objective of this study was to know the antibacterial activity of ethanol extract of Jatropha leaves at concentrations of 20, 40, 60 and 80% against the growth of Pseudomonas aeruginosa. Method, This study used experimental posttest only control group design with disc diffusion method used concentrations of 20, 40, 60 and 80%. Positive control using ciprofloxacin antibiotics and negative control using 96% ethanol. Results, of the study obtained the average diameter of inhibitory zones at concentrations of 20, 40, 60%, and 80% respectively were 11.5 mm, 18.3 mm, 19.5 mm, and 20.7 mm. Respectively the analysis of Least Significant Difference test, it was found that there were significant differences in inhibition zones in each extract concentration. Conclusion, the conclusion of this study is that the ethanol extract of Jatropha leaves has antibacterial activity against the bacterium Pseudomonas aeruginosa. Keywords: Jatropha leaves, extract, antibacterial activity, Pseudomonas aeruginosa